Comparison of Rainfall -Runoff Models with F.J. Mock and NRECA to Determine Water Availability of Rukoh Reservoir, Aceh - Hidayat, Maulana; Nugroho, Hari (Diponegoro University, 2025)
Rukoh Reservoir is located in the upper part of Krueng (Kr.) Rukoh River Watershed, Pidie Regency, Aceh Province with a catchment area of 19.63 Km2. This reservoir has a storage capacity of 124.42 million m3 and is used for irrigation, drinking water and hydropower. The condition of Kr. Rukoh there is no discharge recording device, so to obtain discharge data it is necessary to convert rainfall data into discharge in the form of Rainfall-Runoff Model. The purpose of this research is to calculate the amount of flow discharge and the suitability of the two rainfall-runoff models using the F.J. Mock method and NRECA method with observed discharge. Furthermore, determining the amount of reliable discharge as inflow availability of Rukoh reservoir. This research begins with the collection of rainfall data, evapotranspiration and condition parameters of the Rukoh Reservoir catchment area. The parameters in both models are optimized to obtain the optimal model discharge that is close to the observed discharge data (Qobs). The results of the model suitability test showed that the NRECA model discharge is better compared to the F.J. Mock discharge model, the NSE test value = 0.64 and the correlation test value R = 0.83. Based on the selected discharge model, the calculation obtained the average flow discharge as Rukoh reservoir inflow of 1.13 m3 / sec and 80% water availability of Rukoh Reservoir by 0.58 m3/sec and 90% water availability obtained at 0.43 m3/sec.